Harmfulness awareness and smoking status determinants among university students in Baghdad (Iraq) - Khaleel, Muna Abdulwahab; Hassan, Abbas Abdul-Hussein; Ayad, Zahraa M.; Hajwal, Salim K.; Al-Taee, Mahdi Hamzah; Muhaibes, Fakhria Jaber; Abbas, Alaa Hamza; Ridha-Salman, Hayder (Pharmakeftiki, 2025)
Tobacco use remains one of the most pressing global health challenges. Approximately 80% of smokers worldwide reside in low- and middle-income countries, where the burden of tobacco-related morbidity and mortality is disproportionately high. Cigarette smoking is notably prevalent among university students. This study aimed at investigating and evaluating the awareness and determinants of smoking status within a university student sample, and at examining the association between awareness levels and smoking-related determinants. A descriptive-analytical cross-sectional study was conducted involving 230 university students who smoke, recruited from Baghdad City. Data were collected using a structured questionnaire designed to assess participants’ awareness of smoking-related harms and the factors influencing their smoking behavior. The majority of the participants were male and aged between 18 and 23 years. Most reported smoking cigarettes and hookah, and demonstrated awareness of the harmful effects of smoking, including its role as a major cause of lung cancer, heart disease, and respiratory conditions. The lowest level of agreement was recorded for the statement linking smoking to road traffic accidents. Nearly half of the participants acknowledged that smoking negatively affects family income. Statistical analysis revealed a significant association between students’ awareness and the determinants of smoking status, as well as with their sociodemographic characteristics.